MENIMBANG KESAHIHAN HADIS DALAM PERSPEKTIF SHI’AH IMAMIYAH - Salamah Noorhidayati, Robitoh Widi Astuti, Ahmat Saepuloh (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2020)
The study of Shi’ah is always interesting to be discussed and researched, both in terms of theology and scientific concepts. Shi’ah Imamiyah  whose entire religious building pivots on the Imam, of course, has implications in many ways, including in the hadith field. The position of the Imam as one source of teaching has an impact on the conception of the hadith and its validity criteria. The question is, whether in determining the quality of traditions among Shi’ah refers to the validity of this tradition? How is the process of criticism of hadith that used? And what about the results of the validity test? This article aimed to test the consistency between the validity of the hadith that has been formulated with the implementation process in determining the quality of the hadith. This research is a literature study in the hadith field. Data was collected from various literary works, articles, and other forms of information that were scientific and had a close relationship with the themes discussed. The data obtained were analyzed objectively by comparing one opinion with another, the conclusion was obtained from the research problem. This study concludes: first, in determining the quality of the hadith, the Shi’ah sect is guided by the validity of the formulated Hadith. Second, the assessment of the validity of the hadith through the process of criticism of the narrators in sanad by using their version of the book rija l al-h}adith. However, because the Shi’ah believes that everything sourced from the Imam can be accepted as hujjah, then criticism of the matan is not carried out on the condition that the quality of the sanad is valid. Third, the implementation of the validity of the hadith has implications for the quality of multilevel hadith, namely s}ah}ih}, h}asan, muwaththaq and d}a’if. Keywords: Hadis, Imamiyah, Kesahihan, Kualitas, Shi’ah